Community Development: Concepts and Implementation in Sustainable Development - Malta (Global Writing Academica Researching and Publishing, 2024)
Community development is a key element in achieving sustainable development, which focuses on improving social, economic, and environmental welfare. This article explores the challenges and opportunities in implementing community development concepts, highlighting the importance of community participation, cross-sector collaboration, technology integration, and human rights-based approaches. The method used in this research is a qualitative method with a library research approach. The initial step involves identifying relevant primary and secondary sources from various digital and physical libraries. Then an in-depth analysis of texts related to community development, its concepts, and implementation in the context of sustainable development is carried out. Data was collected from journal articles, books, government reports, and official documents related to community development and sustainable development. The results of this research show that community development is a key element in achieving sustainable development, with a focus on improving social, economic, and environmental welfare. Despite being faced with various challenges, such as social inequality, environmental damage, and political conflict, there are great opportunities to increase the effectiveness of community development through active community participation, cross-sector collaboration, technology integration, and a human rights-based approach.